Dividend Policy and Shareholders’ Wealth: Evidence from Listed Food, Beverage and Tobacco Companies in Sri Lanka - Anandasayanan, S.; Ajintha, P. (Eastern University, Sri Lanka, 2024)
The aim of this study was to investigate the impact of dividend policy on shareholders' wealth, with a specific focus on companies in the food, beverage, and tobacco sectors listed in the Colombo Stock Exchange (CSE). Data were collected from the annual reports of 27 selected companies over a five-year period, spanning from 2017 to 2021. To examine this impact, the study used Dividend per Share, Dividend Pay-out Ratio, and Dividend Yield as explanatory variables. Additionally, Market Price per Share served as a proxy for shareholders' wealth. The study also considered Firm Size and Financial Leverage as control variables to assess their impact of dividend policy on shareholders' wealth. To analyze the data, the study utilized correlation and panel data regression analysis. Before conducting the regression analysis, the Variable Inflation Factor (VIF) test was employed to check for any multicollinearity issues among the explanatory variables. The results showed no significant problems of multicollinearity. Regarding the panel data regression, three different models were used: pooled Ordinary Least Squares (OLS), fixed- effect, and random-effect models. After conducting the analysis, the fixed-effect model was determined to be the most appropriate model for explaining the impact of dividend policy on shareholders' wealth. The results from the fixed-effect model indicated that Dividend per Share positively impacts on shareholders’ wealth. Results supported the signaling theory. As per the signaling theory if Dividend per share increases it will reveal the company’s future prospectus. Therefore investors want to invest in that company’s shares. As a results that company’s share prices increases thus share holders’ wealth maximize. In contrast, Dividend Yield exhibited a negative relationship with shareholders' wealth. Companies may face difficulties in gathering sources of financing during the pandemic situation. So if the companies pay more dividend to their shareholders, mostly they will have to depend on the long term loans for their sources of financing. As a result the companies need to pay higher interest, which will decrease the shareholders’ wealth by reducing the earning per share. These findings will assist to the better management of the companies by taking proper decisions on dividend policies. Also it aids the shareholders as well as the investors to make informed choices regarding their wealth.
Keywords: Dividend policy; Dividend per Share; Shareholders’ Wealth; Colombo Stock Exchange